2013
DOI: 10.1002/stem.1348
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Preclinical Studies on Human Cell-Based Therapy in Rodent Ischemic Stroke Models: Where Are We Now after a Decade?

Abstract: Stroke, a debilitating brain insult, afflicts millions of individuals globally each year. In the last decade, researchers have investigated cell-based therapy as an alternative strategy to improve neurological outcome following stroke. This concise review critically examines preclinical reports using human adult and fetal stem/progenitor cells in rodent models of ischemic stroke. As we enter the second decade of study, we should aim to optimize our collective likelihood to translational success for stroke vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 24 publications
0
58
0
Order By: Relevance
“…Results from stemand immune-cell-based trials suggest that application of cells for diagnostic or therapeutic purposes may help to treat patients with myocardial infarction, stroke, and various neurodegenerative, autoimmune, and inflammatory diseases. [1][2][3][4][5] Efficient noninvasive techniques for in vivo tracking of cells are essential for successful further development of cell-based therapies. An established approach is in vitro cell-labeling with superparamagnetic iron-oxide nanoparticles (SPIO) and their subsequent in vivo tracking by magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…Results from stemand immune-cell-based trials suggest that application of cells for diagnostic or therapeutic purposes may help to treat patients with myocardial infarction, stroke, and various neurodegenerative, autoimmune, and inflammatory diseases. [1][2][3][4][5] Efficient noninvasive techniques for in vivo tracking of cells are essential for successful further development of cell-based therapies. An established approach is in vitro cell-labeling with superparamagnetic iron-oxide nanoparticles (SPIO) and their subsequent in vivo tracking by magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…Manuscripts covered many advances in understanding the fundamental mechanisms that control stem and progenitor cell fate, and advances in working toward treating all tissues, from the lower extremities to the brain. Exciting basic and translational research was reported in using stem cells to treat osteoporosis [11], spinal cord injuries [12,13], radiation-induced fibrosis [14], glaucoma [15], globoid cell leukodystrophy [16], stroke [17], and Huntington's disease [18], to name just a few. It has truly been an exciting year, as we watch the stem cell field explode.…”
mentioning
confidence: 99%
“…In comparison in the chronic stroke phase, improvement in neurological function is likely to be driven by neural replacement, angiogenesis, and neuroplasticity. 9 Stem cells are now recognized to secrete a range of paracrine growth factors, which may modulate neurogenesis, angiogenesis, and immunomodulation. 9,[12][13][14] There are primarily three human tissue sources for stem cell treatments: embryonic, reprogrammed somatic cells, or adult organs.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…9 Stem cells are now recognized to secrete a range of paracrine growth factors, which may modulate neurogenesis, angiogenesis, and immunomodulation. 9,[12][13][14] There are primarily three human tissue sources for stem cell treatments: embryonic, reprogrammed somatic cells, or adult organs. Pluripotent stem cells, namely embryonic or induced pluripotent stem cells, with their wide differentiation potential may also present a risk of tumor formation.…”
Section: Introduction and Rationalementioning
confidence: 99%